2018
DOI: 10.1038/s41598-018-31569-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiosphere-derived cells suppress allogeneic lymphocytes by production of PGE2 acting via the EP4 receptor

Abstract: Cardiosphere-derived cells (CDCs) are a cardiac progenitor cell population, which have been shown to possess cardiac regenerative properties and can improve heart function in a variety of cardiac diseases. Studies in large animal models have predominantly focussed on using autologous cells for safety, however allogeneic cell banks would allow for a practical, cost-effective and efficient use in a clinical setting. The aim of this work was to determine the immunomodulatory status of these cells using CDCs and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…CDCs are a group of CPCs that have the ability to motivate endogenous mechanisms of cardiac repair and attenuate adverse ventricular remodeling 100 , and also have been proven to improve cardiac function in a variety of heart diseases 101 . CDC-derived exosomes (CDC-Exos) could also mitigate the myocardium damage caused by AMI, having the ability to relieve oxidative stress, reduce cell apoptosis and adverse ventricular remodeling, and facilitate angiogenesis after MI 102 - 105 .…”
Section: Immune Cell-derived Exosomes In Immunomodulation After Amimentioning
confidence: 99%
“…CDCs are a group of CPCs that have the ability to motivate endogenous mechanisms of cardiac repair and attenuate adverse ventricular remodeling 100 , and also have been proven to improve cardiac function in a variety of heart diseases 101 . CDC-derived exosomes (CDC-Exos) could also mitigate the myocardium damage caused by AMI, having the ability to relieve oxidative stress, reduce cell apoptosis and adverse ventricular remodeling, and facilitate angiogenesis after MI 102 - 105 .…”
Section: Immune Cell-derived Exosomes In Immunomodulation After Amimentioning
confidence: 99%
“…However we have demonstrated that cryopreservation of dog CDCs does not alter their immunophenotype and cellular characteristics (Dutton et al, 2018a). Furthermore, we have shown at a molecular level that canine CDCs are also immune-privileged similar to the immunomodulatory function of MSCs (Dutton et al, 2018b) and cryopreservation retains this property suggesting they are safe to use in vivo.…”
Section: Human and Canine Dilated And Arrhythmogenic Ventricular Cardmentioning
confidence: 78%
“…Cardiosphere derived cells (CDCs) are cardiac progenitor cells, which can regenerate heart tissue and be used in several cardiac diseases [63]. Given that SARS-CoV-2 can attack cardiac cells and lead to serious cardiovascular complications [42], the application of CAP-1002 can be considered as a candidate treatment in these patients.…”
Section: Allogeneic Cardiosphere-derived Cells (Cap-1002)mentioning
confidence: 99%